Tuned activation of MSLN-CAR T cells induces superior antitumor responses in ovarian cancer models. Issue 2 (6th February 2023) - Schoutrop, Esther; Poiret, Thomas; El-Serafi, Ibrahim; Zhao, Ying; He, Rui; Moter, Alina; Henriksson, Johan; Hassan, Moustapha; Magalhaes, Isabelle; Mattsson, Jonas
Abstract : Background: Limited persistence of functional CAR T cells in the immunosuppressive solid tumor microenvironment remains a major hurdle in the successful translation of CAR T cell therapy to treat solid tumors. Fine-tuning of CAR T cell activation by mutating CD3ζ chain immunoreceptor tyrosine-based activation motifs (ITAMs) in CD19-CAR T cells (containing the CD28 costimulatory domain) has proven to extend functional CAR T cell persistence in preclinical models of B cell malignancies. Methods: In this study, two conventional second-generation MSLN-CAR T cell constructs encoding for either a CD28 co-stimulatory (M28z) or 4-1BB costimulatory (MBBz) domain and a novel mesothelin (MSLN)-directed CAR T cell construct encoding for the CD28 costimulatory domain and CD3ζ chain containing a single ITAM (M1xx) were evaluated using in vitro and in vivo preclinical models of ovarian cancer. Two ovarian cancer cell lines and two orthotopic models of ovarian cancer in NSG mice were used: SKOV-3 cells inoculated through microsurgery in the ovary and to mimic a disseminated model of advanced ovarian cancer, OVCAR-4 cells injected intraperitoneally. MSLN-CAR T cell treatment efficacy was evaluated by survival analysis and the characterization and quantification of the different MSLN-CAR T cells were performed by flow cytometry, quantitative PCR and gene expression analysis. Results: M1xx CAR T cells elicited superior antitumor potency and persistence, as compared with the conventional second generation M28z and MBBz CAR T cells. Ex vivo M28z and MBBz CAR T cells displayed a more exhausted phenotype than M1xx CAR T cells as determined by co-expression of PD-1, LAG-3 and TIM-3. Furthermore, M1xx CAR T cells showed superior ex vivo IFNy, TNF and GzB production and were characterized by a self-renewal gene signature. Conclusions: Altogether, our study demonstrates the enhanced therapeutic potential of MSLN-CAR T cells expressing a mutated CD3ζ chain containing a single ITAM for the treatment of ovarian cancer. CAR T cells armored with calibrated activation potential may improve the clinical responses in solid tumors.